Internalization of Monotheistic (Tawhid) Values in the Process of Strengthening Students' Self-Esteem and Motivation to Learn - Aisyah, Ami Amanda Putri; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
Islamic education is not only oriented towards academic achievement, but also towards the holistic formation of students' personalities, especially in spiritual and psychological aspects. At the senior high school level, students are in a phase of self-identity search that is prone to decreased learning motivation and a crisis of meaning in life. This condition highlights the importance of an educational approach that can instill meaningful basic values. One such approach is the internalization of monotheistic values in Islamic Religious Education. This study aims to analyze the process of internalizing monotheistic values in Islamic Religious Education at Senior High School identify supporting and inhibiting factors, and examine its implications for strengthening students' self-esteem. This study uses a descriptive qualitative method with a phenomenological approach. Data were collected through interviews with students and documentation studies, then analyzed thematically. The results show that the internalization of monotheistic values occurs through the stages of understanding, appreciation, and practice of values in learning and school culture. Supporting factors include religious habits, role models among educators, and contextual learning, while normative approaches and the influence of the social-digital environment are inhibiting factors. The internalization of monotheistic values has implications for strengthening intrinsic learning motivation, psychological resilience, and students' ability to interpret the purpose of learning and life in a more meaningful way.